Organización Contable a la empresa Agro Veterinaria Quezada del cantón Célica. Periodo octubre - diciembre 2022. - Manzanillas Orellana, Alexander Gerardo (2023)
The Curricular Integration Project titled "Accounting Organization of Agro-Veterinary Company Quezada in the Célica Canton. October-December 2022 Period." was carried out with the main objective to investigate the economic and financial situation of the business. This was achieved through the meticulous arrangement of its accounting procedures, providing the owner with information about the progress of their economy in an efficient and effective manner, culminating in precise outcomes. Moreover, this endeavor was instrumental in the accomplishment of the designated specific objectives. In order to achieve the first objective, a plan and account manual were formulated in accordance with the company's requirements. This comprehensive document outlines its assets, liabilities, equity, revenues, costs, and expenses, complete with descriptions and corresponding codes. This enables easy identification during the accounting process. Upon initiating the accounting process, the realization of the third objective was successfully accomplished. This involved the meticulous accomplishment of an initial inventory, accompanied by a physical verification of the company's assets, valuables, rights, and obligations. Based on this, the Initial Statement could be established, reflecting the organization's assets, liabilities, and equity. Essential information was gathered to prepare the operations memorandum, followed by the recording of transactions in the General Journal. Subsequently, these transactions were transferred to the General Ledger, Trial Balance, and Worksheet, where necessary adjustments were made, including the appropriate depreciations. Finally, the Income Statement, the Statement of Financial Position, and the Statement of Cash Flows were prepared, accompanied by their respective explanatory notes. Subsequently, conclusions and recommendations were formulated based on the conducted study. It is worth noting that during the period from October 1st to December 31st, 2022, the Agro-Veterinary company reported a net profit of $ 5.006,04, which is reflected in the Income Statement.